2017
DOI: 10.1093/toxsci/kfx226
|View full text |Cite
|
Sign up to set email alerts
|

Editor’s Highlight: Variation in Methylmercury Metabolism and Elimination Status in Humans Following Fish Consumption

Abstract: Evaluating the potential for methylmercury (MeHg) toxicity relies on accurately predicting the mercury (Hg) body burden that results from eating fish. Hg body burden is directly determined by the slow elimination kinetics of MeHg in the human body (kel = 0.014 days-1 or t1/2 =50 days). Existing studies on MeHg half-life in humans demonstrate a wide range values (t1/2 = 30 to >150 days) and has lead to uncertainty in the derivation of a regulatory standard for acceptable daily oral intake. The causes of variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 41 publications
4
25
0
Order By: Relevance
“…Adult male Pacific walruses weigh up to 2,000 kg and eat approximately 2-3% of their body weight per day (Kastelein et al, 2000). Nevertheless, the range of fecal Hg species among walruses was comparable to values reported among Japanese men (n = 4;Ishihara, 2000) and adults in Rochester, NY (n = 33;Caito et al, 2018;n = 8, Rand et al, 2016) ( (Ishihara, 2000;Rand et al, 2016;Caito et al, 2018). Using an average wet/dry ratio for human fecal samples (4.18 unitless) (Rothenberg et al, 2019), the THg and MeHg concentrations were converted from wet weight to dry weight (see Supplementary Table 12 for THg and MeHg concentrations in wet weight).…”
Section: Mehg Intake and Excretion In Walruses And Humanssupporting
confidence: 80%
“…Adult male Pacific walruses weigh up to 2,000 kg and eat approximately 2-3% of their body weight per day (Kastelein et al, 2000). Nevertheless, the range of fecal Hg species among walruses was comparable to values reported among Japanese men (n = 4;Ishihara, 2000) and adults in Rochester, NY (n = 33;Caito et al, 2018;n = 8, Rand et al, 2016) ( (Ishihara, 2000;Rand et al, 2016;Caito et al, 2018). Using an average wet/dry ratio for human fecal samples (4.18 unitless) (Rothenberg et al, 2019), the THg and MeHg concentrations were converted from wet weight to dry weight (see Supplementary Table 12 for THg and MeHg concentrations in wet weight).…”
Section: Mehg Intake and Excretion In Walruses And Humanssupporting
confidence: 80%
“…Methylmercury, derived from fish, and dimethylmercury are readily absorbed in the gastrointestinal tract. MeHg is slowly demethylated and oxidized to Hg 2+ . Once assimilated into the cell, Hg2+ and MeHg+ form covalent bonds with glutathione and cysteine residues of proteins .…”
Section: Organic Mercurymentioning
confidence: 99%
“…MeHg is slowly demethylated and oxidized to Hg 2+ . 86 Once assimilated into the cell, Hg2+ and MeHg+ form covalent bonds with glutathione and cysteine residues of proteins. 87 Organic Hg is found as the most frequent and most hazardous form of exposure to Hg that is frequently identified as EtHg and MeHg.…”
Section: Organic Mercurymentioning
confidence: 99%
“…Rand et al (2016) reported a high degree of inter-individual variability in the MMHg biotransforma-tion kinetics during a feeding experiment and proposed that the gut microbiome can be a significant modulating factor for MMHg absorption. Later, Caito et al (2018) showed that individuals who received antibiotic therapy had lower MMHg elimination rates than untreated individuals, highlighting the importance of gut microbiota in the elimination of MMHg.…”
Section: Introductionmentioning
confidence: 99%